Neuraminidase Inhibitor-Resistant and -Sensitive Influenza B Viruses Isolated from an Untreated Human Patient - Hurt, Aeron C. (American Society for Microbiology, 2006)
An influenza B virus from an infant with no history of treatment or contact with neuraminidase inhibitors demonstrated a significant reduction in sensitivity to these drugs. Here, we describe the analysis of a mixed viral population that contained a novel D197E amino acid substitution that was responsible for this reduction.